2017
DOI: 10.1371/journal.pntd.0005893
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genomic characterization of tick- and human-derived severe fever with thrombocytopenia syndrome virus isolates from South Korea

Abstract: BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne viral disease caused by the SFTS virus (SFTSV) from Bunyaviridae that is endemic in East Asia. However, the genetic and evolutionary characteristics shared between tick- and human-derived Korean SFTSV strains are still limited.Methodology/Principal findingsIn this study we identify, for the first time, the genome sequence of a tick (Haemaphysalis longicornis)-derived Korean SFTSV strain (designated as KAGWT) and compare this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…The finding of high prevalence and mortality rate in the elderly is in agreement with corresponding data from other studies (30). The phy- logenetic tree of 335 SFTSV strains, including 116 strains identified in this study, revealed that most Korean SFTSVs can be classified into the 6 previously identified genotypes (A-F) (19,26), and the B genotype can be subdivided into at least 3 different genotypes (B-1, B-2, and B-3). Further, inconsistent phylogenetic clustering segments suggested that at least 6 genotypes were co-circulating and 9 reassortments among them in South Korea.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding of high prevalence and mortality rate in the elderly is in agreement with corresponding data from other studies (30). The phy- logenetic tree of 335 SFTSV strains, including 116 strains identified in this study, revealed that most Korean SFTSVs can be classified into the 6 previously identified genotypes (A-F) (19,26), and the B genotype can be subdivided into at least 3 different genotypes (B-1, B-2, and B-3). Further, inconsistent phylogenetic clustering segments suggested that at least 6 genotypes were co-circulating and 9 reassortments among them in South Korea.…”
Section: Discussionsupporting
confidence: 91%
“…These sequences, as well as all known SFTSV full-length sequences available in GenBank, were subjected to phylogenetic analysis ( Figure 2 and Supplemental Figure 2). The results show that Korean SFTSVs can be roughly classified into A-F genotypes based on the classification method previously used in China and Korea (19,26). The majority of Korean SFTSV isolates (n = 92 of 133, 69.2%) were classified as the B genotype.…”
Section: Resultsmentioning
confidence: 88%
“…Notably, for the sequences of the conserved genome segment termini, particularly the S segment, different sequences have been published. For the S segment these sequences differ in the insertion/deletion of an A at position 9, counted from the 5' terminus, or a U in 460 case of the 3' terminus (47)(48)(49). The S segment RNA including the A at position 9 (denoted as 9A) resulted in much stronger polymerase activity of the L protein compared to the Ssegment promoter lacking the 9A, even though the affinity to the L protein seems to be comparable between the two S segment promoters ( Supplementary Figures S5 and S9).…”
Section: The Sftsv L Protein Is An Active Polymerasementioning
confidence: 99%
“…The evidence of tick bites in patients with SFTS based on the detection of ticks on the skin surface and/or detection of possible tick-bite scars was not shown in one half of the SFTS patients in Japan [5]. Furthermore, H. longicornis and A. testudinarium play roles in transmitting SFTSV to humans in Japan, whereas in PR China and South Korea, the main vector involved in transmitting the virus to humans might be H. longicornis [11,13,14].…”
Section: Tick Species Involved In Sftsv Transmission To Humansmentioning
confidence: 95%
“…The SFTSV genome was also detected in the tick species Amblyomma (A.) testudinarium in South Korea and Japan [5,11,12]. The seasonality of SFTS is year-round, but most patients in Japan become ill between spring and autumn.…”
Section: Tick Species Involved In Sftsv Transmission To Humansmentioning
confidence: 99%